Solubility and the periodic table of elements - Gumiski, Cezary (Pure and applied chemistry, 2015)
Interesting general tendencies of changes of solubilities of elements and groups of compounds may be observed when the corresponding solubility data are arrayed according to the increasing atomic number of the elements. Such trends are exemplified with the data of various systems (metallic and salt-water type) evaluated in several volumes of the IUPAC-NIST Solubility Data Series. The solubilities of elements in mercury as well as in liquid alkali metals, when ordered according their atomic numbers, change roughly in a corresponding way as the temperatures and energies of melting or boiling points of the elements. However, majority of transition metals dissolved in alkali metals are subject to some side reactions with nonmetallic impurities that may drastically elevate their concentration levels. The solubilities of intermetallic compounds in mercury depend primarily on the energies of formation of these intermetallics in the binary alloys and then on the dissolution energies of the component metals in mercury. It has been observed that the experimental solubilities of metal halates in water show quite well defined periodical changes. The arrayed solubility data of rare earth metal fluorides and chlorides in water display quite smooth changes with the increasing atomic numbers if the solutes are isomorphic. Some exceptions from the smooth changes for rare earth metal bromides and iodides are explained. These general observations are useful in evaluating and predicting solubilities in experimentally unknown systems.